2007
DOI: 10.1111/j.1447-0756.2007.00629.x
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopy should be strongly considered for women with unexplained infertility

Abstract: Laparoscopy should be strongly considered for examining women with unexplained infertility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0
8

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 24 publications
1
41
0
8
Order By: Relevance
“…peritubal adhesions were identified in 29%-41% of the cases (Drake et al 1997;Sandra et al 2003;Nakagawa et al 2007). Sandra et al (2003) reported that diagnostic laparoscopy changed the management plan in 25% of infertile patients with normal HSG findings; our findings were the same.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…peritubal adhesions were identified in 29%-41% of the cases (Drake et al 1997;Sandra et al 2003;Nakagawa et al 2007). Sandra et al (2003) reported that diagnostic laparoscopy changed the management plan in 25% of infertile patients with normal HSG findings; our findings were the same.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore concluded that diagnostic laparoscopy is a reliable procedure in detecting abnormalities and in contributing to the management plan in this patient population. Nakagawa et al (2007) performed diagnostic laparoscopy for unexplained infertility patients and compared the pregnancy rate following laparoscopic surgery with that following ART treatment performed in the same center for patients of different age groups. Because they obtained a significantly higher pregnancy rate following laparoscopy (75%) than following ART treatment (33.3%) in women 26-30 years of age, they stressed the importance of performing diagnostic laparoscopy in infertile patients with unexplained infertility.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, laparoscopy was able to correctly diagnose pathology in 62 (75.6%) patients. In 2007, Nakagawa K et al strongly recommended diagnostic laparoscopy for unexplained infertile patients because of the high rate of abnormal findings (87%) on laparoscopy (34). In a cross-sectional study in 2009, Kahyaoglu S et al evaluated the treatment strategy change after diagnostic laparoscopy for primary and secondary unexplained infertile patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is no information concerning the accuracy, reliability, prognosis or effectiveness of the procedure. Several studies have reported pregnancy rates after laparoscopy for patients with infertility of unexplained etiology (Cundiff et al 1995;Nakagawa et al, 2007). However, there are no reports that relate pregnancy outcomes to significant results found inside the fallopian tube.…”
Section: Advanced Gynecologic Endoscopy 150mentioning
confidence: 95%